HISTOPATHOLOGICAL SPECTRUM OF PROSTATIC LESIONS AND THEIR CORRELATION WITH SERUM PROSTATE SPECIFIC ANTIGEN LEVELS - Pushpa; Goyal, Namita; Ritul; Bhamu, Sukharam (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The present study is conducted to find out the histopathological spectrum of different prostatic biopsies and compare them with respective serum prostate-specific antigen (PSA) levels and grading, scoring of malignant lesions according to Gleason’s group grading system. Methods: A total 165 prostatic biopsies from patients of >50 years of age groups were included in the study. This cross-sectional study was conducted in the Department of Pathology, R.N.T. Medical College, Udaipur, over a period of 1 year. The specimens were examined for various prostatic pathologies by doing histopathological examination and their serum PSA values were correlated. Results: On histopathological examination, 76.9% of cases were of benign lesions, 14% of cases had prostatic malignancy, 6.6% of cases of inflammatory lesions, and 2.4% of cases of prostatic intraepithelial neoplasia. Majority of inflammatory lesions, prostate intraepithelial neoplasia, benign prostatic hyperplasia (BPH), and BPH with prostatitis had PSA level <4 ng/mL. In malignant cases, majority had PSA levels above 10 ng/mL. In prostatic adenocarcinoma, 56.32% of cases were found moderately differentiated grade (G2) followed by 30.43% of cases were of well-differentiated grade (G1) and 13.04% of cases of poorly differentiated grade (G3-G4). Conclusion: The study showed a statistically positive correlation between histological diagnosis and serum PSA level.